The Semantic-Pragmatic Characteristics of the Speech Act of Self-praise. - Gasparyan, Narine (Bulletin of Yerevan University B: Philology, 2025)
The purpose of the article is to present the semantic and pragmatic features ofspeech acts expressing self-praise. Unlike praise, self-praise has a negativeconnotation. It can be expressed through different perlocutionary acts. The purposeof this act is to gain attention and admiration, trying to please the listener and gain hisapproval with his verbal and non-verbal behaviour, pleasing the addressee. Whileperforming this act, the speaker highlights his merits, successes, skills and qualitiesin order to present them in a positive light. Self-praise is a type of praise when thespeaker addresses a positive assessment to himself, that is, in this case, therecipient of the self-praise acts as the recipient of the praise at the same time. Hetries to strengthen his self-esteem, impress others, and establish authority. If self-praise is modest and consistent with the context, it can strengthen the person'sauthority, while excessive self-praise can be perceived as arrogance. The intentionof a self-praising person is to achieve his goal by trying to gain the approval of theinterlocutor, as a result of which his verbal and non-verbal behavior can beexpressed even in self-deprecation by using self-humiliating expressions. Theimplementation of this act is conditioned by the different status and rolecharacteristics of the communicators. The present paper is an attempt to outline thesemantic and pragmatic peculiarities of these speech acts.
Keywords: speech act; self-praise; perlocutive result; communicative purpose; illocutive intention; addressee